Microclimate Simulation-Based Architectural Learning Model in Urban Design Studio: A Quasi-Experimental Approach to Enhancing Design Quality and Thermal Comfort - Purnama Sakhrial Pradini; Harry Miarsono (CV. Creative Tugu Pena, 2026)
Urban overheating and outdoor thermal discomfort have become critical challenges in rapidly urbanizing tropical cities, significantly reducing the environmental quality, usability, and livability of public spaces. Despite the growing emphasis on climate-responsive and performance-based urban design, the integration of environmental simulation into urban design education and spatial decision-making processes remains limited. This study aims to evaluate the effectiveness of a simulation-informed urban design learning model in improving both design quality and outdoor thermal comfort performance. A quasi-experimental approach was employed within an urban design studio involving 40 architecture students divided into control and experimental groups. The experimental group applied a simulation-informed workflow using ENVI-met and Ladybug Tools, while the control group followed conventional urban design methods. Design quality was evaluated through spatial organization, public-space quality, climate responsiveness, vegetation integration, and design coherence. The results demonstrate that the experimental group achieved a 39.6% improvement in overall design quality, with the highest increase observed in climate responsiveness (60.7%). In terms of thermal performance, the simulation-informed approach reduced air temperature by 4.3°C and MRT by 9.5°C, while increasing shading coverage by 30%. Statistical analysis confirms that the differences between groups are significant (p < 0.05). The findings indicate that environmental simulation substantially enhances spatial responsiveness and thermal performance by enabling iterative and evidence-based design decisions. This study contributes to performance-based urban design and architectural pedagogy by establishing a quantitative relationship between microclimate simulation,